2001
DOI: 10.1097/00005768-200105000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss methods of high school wrestlers

Abstract: The majority of Michigan high school wrestlers engaged in at least one potentially harmful weight loss method each week of the wrestling season. Fasting and various methods of dehydration were the primary methods of rapid weight loss. Wrestlers who lost weight each week were more likely to binge eat. Potentially harmful weight loss practices were found to be common at all grades and success levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
91
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 5 publications
5
91
0
Order By: Relevance
“…The athletes were evaluated in preparatory season, and it was observed that all of them were above the upper threshold of body mass in their categories (4.4 ± 2.4%), with amplitude range between 1.0% and 9.2%. These values are compatible with what was reported in other modalities such as Olympic wrestling 6,21,42 . The fact that the athletes were above the upper threshold of the competitive category deserves attention, since fast decrease in body mass in order to fit in their categories may bring damage to health 43 and harm performance 44 , especially due to the fact that these athletes present fat mass compatible with the indications for fighters and predominant mesomorphic component.…”
Section: Discussionsupporting
confidence: 92%
“…The athletes were evaluated in preparatory season, and it was observed that all of them were above the upper threshold of body mass in their categories (4.4 ± 2.4%), with amplitude range between 1.0% and 9.2%. These values are compatible with what was reported in other modalities such as Olympic wrestling 6,21,42 . The fact that the athletes were above the upper threshold of the competitive category deserves attention, since fast decrease in body mass in order to fit in their categories may bring damage to health 43 and harm performance 44 , especially due to the fact that these athletes present fat mass compatible with the indications for fighters and predominant mesomorphic component.…”
Section: Discussionsupporting
confidence: 92%
“…Other investigations also proved that a hypocaloric diet, higher volume of exercises, and food restriction were the most often applied methods for body weight reduction among judo competitors [15,20]. In wrestling [23,24] and other combat sports [19], studies have found that increased exercise and food restriction were the primary strategies for body weight reduction.…”
Section: Discussionmentioning
confidence: 96%
“…We could not directly assess possible weight cycling behavior during the sport career in our sample, but weight cycling and unhealthy weight control methods ('weight cutting') have been widely reported in young male athletes participating in wrestling [24][25][26][27][28] and other sports with weight classes. 29 Over 80% of high school 25 and college 26 wrestlers have been reported to 'cut weight', and 26.6% to cut more than 10 times per season.…”
Section: Discussionmentioning
confidence: 99%